Pelatihan dan Pendampingan Penyusunan RPJMDesa Berbasis Partisipatif di Desa Lokasari, Sidemen, Karangasem, Bali - Bandiyah Bandiyah (Jurnal Pengabdian Pada Masyarakat, 2016)
RPJMDesa preparation training activities aimed at providing convenience in writing, analytical planning techniques and solutions to the problems faced by rural development, in particular villages are lagging as Lokasari village of Sidemen subdistrict, Karangasem. In addition, to help ease the task of national and local governments in order to generate output RPJMDesa quality and right on target. Activity methods used are in the form of training and guidance by referring to the analysis of alternatif plans and follow the trouble shooting on each field in the village unit with a participatory basis. The output of this activity first, village officials are very enthusiastic in learning the methods of preparation RPJMDesa being perceived as the new knowledge. Second, this method is easily prepared and applied in RPJMDesa. Third, village officials and community broaden the knowledge and scientific language that has not been previously known. Outcome activity is becoming a driving force and assisting consultants for villages that have not been independently.